Alteration of biomarkers of expired and cured COVID- 19 ICU patients in a tertiary care hospital: Alteration of biomarkers of expired (Bioresearch Communications, 2021)
Coronavirus Disease 2019 (COVID-19) is a respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2). This is a retrospective observational study aimed to find the alteration of some biochemical and hematological parameters of 121 COVID-19 patients admitted in intensive care unit (ICU) of Evercare Hospital Dhaka during May to December 2020.Methods: Retrospective biochemical, hematological and molecular (COVID-19 RT-PCR Ct value) markers were analyzed on COVID-19 patients in ICU and compared on those who died in the ICU and those cured.Results: Comparison of viral titer assessed by RT-PCR Ct values of target genes of SARS-CoV-2 among cured and expired patients did not show any significant differences. However, biochemical parameters such as CRP, Ferritin and hematological parameters such as WBC, absolute neutrophil, absolute lymphocyte, D-dimer showed significant differences among cured and expired patients. Patients who died in ICU mean CRP, Ferritin, D-dimer, WBC, absolute neutrophil were 10.39, 7694.30, 3196, 16.38, 15.12 respectively, compared to cured patients 0.93, 457.57, 773, 11.24, 8.86 respectively, with 95% confidence interval (95% CI). Platelets and absolute lymphocytes were observed decreased in expired patients compared to cured. Further, elevated level of neutrophil to lymphocyte ratio (NLR) and reduced level of lymphocyte to C-reactive protein ratio (LCR) has significant correlation with disease severity.Conclusion: These findings indicate that biochemical parameters such as CRP, Ferritin and hematological parameters such as CBC, D-Dimer, NLR, LCR can be monitored to identify severity and fatality of COVID-19 patients and thus, may help in improving disease outcome.Bioresearch Commu. 7(2): 1031-1037, 2021 (June)